Cover Picture: Enforced Electronic‐Donor‐Acceptor Complex Formation in Water for Photochemical Cross‐Coupling (Angew. Chem. Int. Ed. 17/2023). Issue 17 (8th March 2023) - Tian, Ya‐Ming; Hofmann, Evamaria; Silva, Wagner; Pu, Xiang; Touraud, Didier; Gschwind, Ruth M.; Kunz, Werner; König, Burkhard
Abstract : The sugar alcohol meglumine enhances the solubility of organic compounds in water and enforces the formation of electron donor–acceptor (EDA) complexes, enabling photochemical C−C and C−S cross‐coupling transformations without sensitizers. The light‐driven redox‐neutral protocol connects haloarenes with indoles, anilines, anisoles, and thiols, as reported by Burkhard König and co‐workers in their Research Article (e202218775 ).